1988
DOI: 10.1002/jsfa.2740420309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phospholipid on the formation of volatile heterocyclic compounds in heated aqueous solutions of amino acids and ribose

Abstract: The concentrations of 68 heterocyclic compounds produced by heating a series of amino acid-ribose and lecithin-amino acid-ribose reaction mixtures at 140°C for 1 h were measured, after headspace collection on Tenax GC, by capillary gas chromatography-mass spectrometry. The amino acids studied were glycine, lysine and cysteine, and the classes of heterocyclic compounds quantified were pyrazines (14), pyridines (7), jkrans (14), thiophenes (26) and thiazoles (7). The studies showed that the addition of lecithin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 18 publications
3
55
0
1
Order By: Relevance
“…These disulfides exhibit, in general, meaty, roasted aromas and their formation is influenced by phospholipids. Other heterocyclic compounds are quenched, too, by the presence of lecithin in the Maillard reaction (Whitfield et al, 1988). Also, unsaturated fatty acids or fatty acid esters impeded the formation of many volatiles including 2-methyl-3-furanthiol and 2-furanmethanethiol in a heated aqueous L-cysteine/ribose system .…”
Section: Interaction Of the Maillard Reaction And Lipid Oxidationmentioning
confidence: 99%
“…These disulfides exhibit, in general, meaty, roasted aromas and their formation is influenced by phospholipids. Other heterocyclic compounds are quenched, too, by the presence of lecithin in the Maillard reaction (Whitfield et al, 1988). Also, unsaturated fatty acids or fatty acid esters impeded the formation of many volatiles including 2-methyl-3-furanthiol and 2-furanmethanethiol in a heated aqueous L-cysteine/ribose system .…”
Section: Interaction Of the Maillard Reaction And Lipid Oxidationmentioning
confidence: 99%
“…2,3-dihydro-6-methylthieno [2,3c] 41 found that concentrations of nitrogen-containing heterocyclic compounds were reduced in systems containing cysteine and ribose, compared with other amino acids. Five thiazoles, including a series of acylthiazoles [16,42,44, 53] and a benzothiazole [75], were generated in the 5'-IMP/cysteine mixtures.…”
mentioning
confidence: 99%
“…Four alkylfurans containing chains of C1-C5 [18,24,41,45], together with two furylketones [34,51] and two acylfurans [27,39] were formed. Another group of furans identified were furfural [15] and its derivatives [30,32,48, 64] and 4-hydroxy-5-methyl-3(2H)-furanone [21].…”
mentioning
confidence: 99%
“…Furfural, an important intermediate in Maillard reaction, can be formed from ribose following a pathway involving the elimination of a hydroxyl group from the 1, 2-enediol form of the Amadori rearrangement product (ARP) to give 3-deoxypentose which yields furfural through dehydration and cyclisation (Whitfield et al, 1988). Furfural can also be derived from ribose directly via two steps of dehydration in acidic systems.…”
Section: Miscellaneousmentioning
confidence: 99%
“…3-Mercapto-2-pentanone and 2-mercapto-3-pentanone are reduction products from 2, 3-pentanedione, which is the degradation product from HMF (Whitfield, Mottram, Brock, Puckey, & Salter, 1988). As shown in Table 2, 3-mercapto-2-pentanone favoured in SC-CO 2 and large amount of ribose presented, while the formation of 2-mercapto-3-pentanone was inhibited in SC-CO 2 -treated mixtures at reactant ratios of 3:1 and 1:1.…”
Section: Thiolsmentioning
confidence: 99%